1997
DOI: 10.1016/s0020-7292(97)00168-9
|View full text |Cite
|
Sign up to set email alerts
|

Community contact persons promote utilization of obstetric services, Anambra State, Nigeria

Abstract: Community contact persons can perform a valuable role in facilitating referral of women with obstetric complications and supporting health education activities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 2 publications
1
18
0
Order By: Relevance
“…Directing TBAs to promote facility services without additional activities does not increase skilled birth attendance, as shown by Kumar [63] and Schooley et al [64]. In Nigeria, TBAs initially referred 54% of women and were pleased that SBAs gave their clients "special and urgent attention" [65]; however, their promotional activities virtually ceased after 6 months. Traditional birth attendant integration mechanisms were rarely applied in isolation.…”
Section: Inclusion Criteriamentioning
confidence: 99%
See 3 more Smart Citations
“…Directing TBAs to promote facility services without additional activities does not increase skilled birth attendance, as shown by Kumar [63] and Schooley et al [64]. In Nigeria, TBAs initially referred 54% of women and were pleased that SBAs gave their clients "special and urgent attention" [65]; however, their promotional activities virtually ceased after 6 months. Traditional birth attendant integration mechanisms were rarely applied in isolation.…”
Section: Inclusion Criteriamentioning
confidence: 99%
“…Nwakoby et al [65] reported an increase in referrals, from 0% to 54%, and Mullany et al [38] reported increased skilled birth attendance, from 5% to 48.7%, with careful selection of TBAs based on combinations of literacy, activity level, gender, self-nomination, and reputation. Notably, studies selecting TBAs exclusively by activity level or popularity changed skilled birth attendance little [14,45,61].…”
Section: Inclusion Criteriamentioning
confidence: 99%
See 2 more Smart Citations
“…Likewise, the National Perinatality Program of Mali was conceived in 1994 and organised the referral system to improve the environment of perinatal care. Reported interventions at the community level focused on (1) educational activities to raise awareness of danger signs and encourage the use of obstetric services; (2) reducing geographical and financial barriers through emergency loan schemes / subvention and (3) improving transport and communication [Kandeh et al, 1997;Nwakoby et al 1997]. This policy led to an increase in cesarean delivery rates in rural district hospitals [De Brouwere, 1997], but it was very difficult to implement in large cities like Bamako.…”
Section: Referral System and Cesarean Deliverymentioning
confidence: 99%